A sensemaking perspective on the roll-out of transdisciplinary learning communities in an academic environment from Bolivia. Issue 7 (3rd October 2022) - Peres-Cajías, Guadalupe; Bauwens, Joke; Craps, Marc; Loots, Gerrit
ABSTRACT: Through a sensemaking lens, this article investigates the concrete appropriation of the so-called transdisciplinary learning communities-approach (TLC for short) as part of a Flemish–Bolivian university cooperation project for development. The article has its empirical basis in ethnographic research conducted between 2017 and 2020 on four campuses of the Bolivian university UCB. The primary data is the so-called organisational talk, gathered through interviews, participant observations, and meetings with Bolivian university staff members who are the main players involved in the Flemish–Bolivian university cooperation project. The analysis suggests that an informal, horizontal, and symmetrical style of organisational communication between organisational members seems to have a positive impact on the appropriation of TLC, which in turn leads to more successful experiences of cooperation with communities and other external partners in the social environment.